2018
DOI: 10.1155/2018/7872036
|View full text |Cite
|
Sign up to set email alerts
|

Application of Wavelet and EEMD Joint Denoising in Nonlinear Ultrasonic Testing of Concrete

Abstract: e health state of concrete is deteriorating during its service. Nonlinear ultrasonic detection based on the amplitude of the fundamental and the second harmonic is considered to be a powerful tool for the discovery of the microcrack in concrete. However, the research on processing the nonlinear ultrasonic signal is still insufficient. In order to highlight the real frequency domain components in the nonlinear ultrasonic signal, wavelet and ensemble empirical mode decomposition (EEMD) were joined to denoise the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The settings of main factors, including the sequence length, code element length, and pair number of magnets would affect the interval and SNR of echoes. Some popular signal processing methods were used to process ultrasonic signals, such as the integration of ensemble empirical mode decomposition and wavelet transform (WT) [11], fractal denoising [12], fractional differential method [13]. Dragomiretskiy and Zosso [14] proposed the variational mode decomposition (VMD) to decompose the raw signal as some band-limited intrinsic mode functions.…”
Section: Related Workmentioning
confidence: 99%
“…The settings of main factors, including the sequence length, code element length, and pair number of magnets would affect the interval and SNR of echoes. Some popular signal processing methods were used to process ultrasonic signals, such as the integration of ensemble empirical mode decomposition and wavelet transform (WT) [11], fractal denoising [12], fractional differential method [13]. Dragomiretskiy and Zosso [14] proposed the variational mode decomposition (VMD) to decompose the raw signal as some band-limited intrinsic mode functions.…”
Section: Related Workmentioning
confidence: 99%
“…VMD has advantages in processing nonstationary signals and suppressing noise.The above decomposition and denoising methods have good denoising effects, but they also have some shortcomings. In recent years, an increasing number of studies have shown that hybrid denoising methods have better performance than single denoising algorithms ( Cao et al, 2021 ; Nie, Wang & Zhao, 2018 ; Fu et al, 2020 ). To effectively decompose and denoise sea cucumber aquaculture water quality data, this article applied a hybrid algorithm combining variational mode decomposition (VMD) and wavelet threshold denoising (WTD) to realize the denoising processing of water quality data.…”
Section: Introductionmentioning
confidence: 99%
“…us, it is difficult to distinguish the material nonlinearity from the obtained nonlinearity in experiment. In general, the numerical method can be considered as an effective method for the nonlinear ultrasonic study [35][36][37][38][39]. By finite element simulations, the motion of interface obeys the contact laws, and the nonlinear effects of ultrasonic waves can be obtained.…”
Section: Introductionmentioning
confidence: 99%